How is body orientation controlled during somersaulting? - Bardy, B. G.; Laurent, M. (Journal of Experimental Psychology: Human Perception and Performance, 1998)
How body orientation is controlled during somersaulting was investigated in 2 experiments that analyzed the kinematics of 223 backward standing somersaults. In Experiment 1, open-loop, initial-condition (flight duration), and prospective (time to contact, or TC1) control strategies were tested as candidates for the regulation of body moment of inertia during the jump. Decreasing between-trials variability of body orientation over time as well as a negative correlation between body angular velocity and TC1 suggested that the moment of inertia was regulated prospectively. In Experiment 2, the visual basis for this regulation was examined by asking experts and novices to execute somersaults either with eyes closed or open. Results showed that the prospective regulation observed in the vision condition disappeared in the no-vision condition with the experts, arguing in favor of a visual control during the jump. Such a coupling was absent with the novices, thus illustrating the role played by the perception-action cycle in the learning process. (PsycINFO Database Record (c) 2012 APA, all rights reserved) https://www.researchgate.net/publication/13657959_How_Is_Body_Orientation_Controlled_during_Somersaulting